Educandos e educadores : imagens refletidas : estudo do processo de constituição de categoria ocupacional - Santos, Arlete Inacio dos (2006)
In the present dissertation, I propose to study the investment made by social educators aiming to the acknowledgement of their occupational category. This investment lays the foundations for the struggle to legitimate their work practice, if compared to other service renders dedicated to the so-called segment child or adolescent in situation of risk. For this purpose, I have decided to analyse the Associação Metodista de Ação Social (Methodist Association for Social Action), located in Niterói - RJ, so as to demonstrate the panorama of the relationship between powers which are inherent in the constitution of the occupational category, as well as the corresponding or coadjuvant institutions that welcome and legitimate the abovementioned educators. For instance, the panorama in which institutional agents produce both their own and the equivalent institutions' social ackowledgement. The expression categoria ocupacional (occupational category) is used in order to outline the reach and the limits of the investments in collective actions objectified by those educators, despite being dependent on organisational methods of institutions, in general philanthropic ones, which establish the entering in the activity plus the required conditions of academic background and specialised knowledge. To meet the objectives settled in the corresponding field research, I have opted to study the constitution of the career of those who work as social educators in the referred institution. From this perspective, I'm able to depict one of its paradigmatic aspects: the changing process from pupil to educator, resulting from the investment in the constitution and reproduction of these institutional spaces.